2020
DOI: 10.1101/2020.07.24.218065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DLX5/6GABAergic expression affects social vocalization: implications for human evolution

Abstract: DLX5 and DLX6 are two closely related transcription factors involved in brain development and in GABAergic differentiation. The DLX5/6 locus is regulated by FoxP2, a gene involved in language evolution and has been associated to neurodevelopmental disorders and mental retardation. Targeted inactivation of Dlx5/6 in mouse GABAergic neurons (Dlx5/6VgatCre mice) results in behavioural and metabolic phenotypes notably increasing lifespan by 33%.Here, we show that Dlx5/6VgatCre mice present an hyper-vocalization an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…The transcription factor Foxp2 is involved in setting up the neuronal circuitry for vocal learning in mammals and is thought to have played a special role in the evolution of human speech and language [34]. And it is also associated with inherited dyspraxia and poor control of the facial musculature [35]. Satb2, an uplayer marker [36], was detected at this time point as well (Figure 1(j)).…”
Section: Generation Of Human Cerebral Organoids Cultured Inmentioning
confidence: 88%
“…The transcription factor Foxp2 is involved in setting up the neuronal circuitry for vocal learning in mammals and is thought to have played a special role in the evolution of human speech and language [34]. And it is also associated with inherited dyspraxia and poor control of the facial musculature [35]. Satb2, an uplayer marker [36], was detected at this time point as well (Figure 1(j)).…”
Section: Generation Of Human Cerebral Organoids Cultured Inmentioning
confidence: 88%
“…We expect future work to continue revealing the relevance of genes implicated in neurodevelopmental disorders to understand domesticated phenotypes (for a salient recent example, see 126 ). Of note, Levi 127 found that the protein coded for by a gene on the WBSCR (GTF2I) binds a locus associated with DLX5/6, a region of the genome associated with a hypersocialization and hypervocalization in mice. Likewise, genes regulated by genes on WBSCR (such as those studied in 56 ) deserve closer attention.…”
Section: Multiple Mechanismsmentioning
confidence: 99%